The “ins” and “outs” of person perception: The influence of consonant wanderings in judgments of warmth and competence - Garrido, Margarida (2019)
In five studies (N=638), we extended the in-out effect to person perception, examining the influence of oral approach-avoidance movements activated by word articulation, on preference, sociability and competence judgments of mock-usernames. Users with inward, in contrast to outward-usernames, were always preferred and judged as warmer. However, they were judged as equally competent. The differential impact of the in-out effect in the core dimensions of social perception suggests that the phenomenon relies on the affective mechanism of approach-avoidance that is only pertinent to judgments related to the warmth dimension. The present research provides further support for the link between the activation of oral muscles and impression formation, emphasizing the relevance of the in-out effect for the person perception domain and embodied social cognition.